Recent trends in nitrogen cycle and eco-efficient nitrogen management strategies in aerobic rice system - Farooq, Muhammad Shahbaz; Wang, Xiukang; Uzair, Muhammad; Fatima, Hira; Fiaz, Sajid; Maqbool, Zubaira; Rehman, Obaid Ur; Yousuf, Muhammad; Khan, Muhammad Ramzan (Frontiers in Plant Science, 2022)
Rice (Oryza sativa L.) is considered as staple food for more than half of the global population and sustaining productivity under scarcity of resources is challenging to meet future food demands of the inflating global population. Transformation (aerobic rice) has been brought in traditional rice system to increase resource-use efficiency, however, literature regarding the pathways of nitrogen (N) cycle and increasing N-use efficiency in aerobic rice system is limited. Excessive application of N-fertilizers improves aerobic rice growth and yield, but at the cost of economic and environmental challenges. This article investigates the major challenge of low N-use efficiency and change in major pathways of N-cycle in aerobic rice system, thereby suggest the agronomic management approaches to improve N-use efficiency. Major objective of this review is optimizing the N-fertilization while sustaining the productivity and environmental safety. Hence, enhancing N-use efficiency in aerobic rice system has become urgently needed for the development of sustainable aerobic rice system. This review elaborates that different soil conditions significantly shift the N-dynamics via changes in major pathways of N-cycle. This study comprehensively reviews the facts why N-losses are high under aerobic rice system, how it can become an eco-efficient production system through agronomic management measures, and which factors hinder in attaining high N-use efficiency. The findings explore the interactive mechanisms of how proper management of N-cycle pathways can be accomplished via optimized N-fertilizer amendments. Several agricultural and agronomic approaches such as site-specific N-management, integrated N-management (INM), and incorporation of enhanced-use efficiency N-fertilizers are suggested that may interactively improve the N-use efficiency and plant N-uptake. Moreover, resource conservation practices such as plant residue management, green manuring, improved genetic breeding, and precision farming are essential to enhance N-use efficiency. It is concluded that after careful insights into the advances in pathways of N-cycle, and incorporation of the suggested agronomic adjustments can reduce N-losses, thereby enhance N-use efficiency while sustaining the aerobic rice productivity and environmental safety. Future research on N-dynamics is encouraged focusing on the interactive evaluation of shifts among activities and diversity of microbial communities, N-use efficiency, and plant demands while applying N-management measures.